2004
DOI: 10.1097/00005176-200411000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum Protein Concentrate Enhances Intestinal Adaptation After Massive Small Bowel Resection in Juvenile Pigs

Abstract: In an animal model of SBS, CPC supplementation of polymeric infant formula resulted in normal weight gain and features of enhanced morphologic adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…The sham group also had a significantly lower mean weight than the NOC group at the five-week and six-week time-points (p = 0.041 and p < 0.0001). 18 Examination of feed intake showed that, although piglets in the SBR group consumed equal energy per kg per day, their total energy consumption was reduced when compared with the NOC and sham groups due to their decreased weight. Piglets in the SBR group failed to resolve diarrhea at either the two-week (p = 0.002 and p = 0.005) or sixweek (p < 0.0001) time-points (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sham group also had a significantly lower mean weight than the NOC group at the five-week and six-week time-points (p = 0.041 and p < 0.0001). 18 Examination of feed intake showed that, although piglets in the SBR group consumed equal energy per kg per day, their total energy consumption was reduced when compared with the NOC and sham groups due to their decreased weight. Piglets in the SBR group failed to resolve diarrhea at either the two-week (p = 0.002 and p = 0.005) or sixweek (p < 0.0001) time-points (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies used domestic pigs or piglets [5,13,16,17,18,19] mainly of female gender [10,13,16,18,20,21,22,23,24,25,26,27,28,29]. Regarding the exact breed, mostly landrace [10,21,22,30,31] or landrace × large white [5,13,16,20,24,26,32,33,34] animals were used.…”
Section: Resultsmentioning
confidence: 99%
“…Colostrum supplement induces muscular hypertrophy increasing the muscle width and the number of cells and these changes may be mediated by the simultaneous increase of the serum concentrations of IGF-1 and IGF binding proteins after small intestinal resection in piglets (176). In a pig model of SBS colostrum induced intestinal adaptation, the piglets that underwent massive intestinal resection showed the same weight gain and greater villus length and crypt depth in the jejunum and ileum compared to the control (177). On the contrary, in a randomized controlled trial Lund et al, observed that in spite of it high content of bioactive factors, colostrum did not significantly increase intestinal functions, absorption and body composition compared with the control (178).…”
Section: Short Bowel Syndrome (Sbs)mentioning
confidence: 97%